Formulation of Antioxidant Cream from Mung Bean (Vigna radiata L.) Seed Coat Extract - Hermanus Ehe Hurit; Linda Handayani; Reinaldo Pradana; Dara Andini Putri (Tropical Biopharmaca Research Center, IPB University, 2026)
The skin is the body’s primary barrier against free radicals, which can induce oxidative stress and premature ageing. Antioxidants neutralize these radicals. This study aims to formulate and evaluate a cream containing ethanol extract of mung bean (Vigna radiata L.) seed coat. Four formulations were prepared with extract concentrations of 10%, 15%, 20%, and 25%. Physical evaluations included organoleptic tests, homogeneity, pH, viscosity, cream type, spreadability, and adhesiveness. Antioxidant activity was measured using the DPPH method. All formulations met physical standards, and formula F4 (25%) showed the highest antioxidant activity with an IC₅₀ value of 79.49 ppm. These findings indicate the potential of mung bean seed coat extract as an active antioxidant agent in topical preparations.